Efficacy and Safety of Triple Combination Cystic Fibrosis Transmembrane Conductance Regulator Modulators in Patients With Cystic Fibrosis: A Meta-Analysis of Randomized Controlled Trials - Wang, Yizi; Ma, Bin; Li, Wenya; Li, Peiwen (Frontiers in Pharmacology, 2022)
Background: Cystic fibrosis is a rare, recessive, progressive genetic disease caused by dysfunction of the cystic fibrosis transmembrane conductance regulator (CFTR) protein. Small molecules have recently been developed to treat the molecular consequences of CFTR mutations and restore CFTR protein function. However, the data on triple combination therapy (mainly from Vertex Pharmaceuticals, which is most tested in clinical trials) are limited. This meta-analysis was aimed to assess the efficacy and safety of this therapy according to different mutation genotypes and comparators. Methods: Relevant publications were identified through searching several medical databases before 31 December 2021. The primary outcomes of ppFEV1, sweat chloride concentration and Cystic Fibrosis Questionnaire-Revised (CFQ-R) score were pooled and analyzed. The secondary outcomes were adverse events in triple combination therapy. Results: Six randomized controlled trials were eligible for analysis. The total outcome of the ppFEV1 change was higher with triple combination therapy than triple placebo or active control (mean difference, MD, 13.6% and 8.74%, respectively). The pooled result of sweat chloride concentrations with triple combination therapy was lower than that of triple placebo or active control (MD, −44.13 and −39.26, respectively). The pooled estimate of the CFQ-R score was higher with triple combination therapy than triple placebo or active control (MD, 19.8% and 14.63%, respectively). No clear differences in adverse events were found between triple combination therapy and the control (placebo or active control). Conclusion: CFTR modulators in triple combination achieve better clinical results than placebo and active control, and result in comparable adverse events. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021293402, identifier PROSPERO 2021 CRD42021293402.